2020
DOI: 10.1093/nar/gkaa454
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory sharing between estrogen receptor α bound enhancers

Abstract: Abstract The human genome encodes an order of magnitude more gene expression enhancers than promoters, suggesting that most genes are regulated by the combined action of multiple enhancers. We have previously shown that neighboring estrogen-responsive enhancers exhibit complex synergistic contributions to the production of an estrogenic transcriptional response. Here we sought to determine the molecular underpinnings of this enhancer cooperativity. We generated g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Lineage-specific oncogenes are known to be driven by condensed clusters of enhancer elements, namely super-enhancers or stretch enhancers 55 , 56 , 57 , yet the hierarchical structures for most of these enhancer clusters remain largely unknown. We show that the enhancer cluster co-amplified with SOX2 in squamous cancer is predominantly driven by a single enhancer e1, which aligns with previous findings of predominant enhancers in other enhancer clusters 58 , 59 . Within the SOX2 enhancer cluster, all the remaining enhancers physically interact with e1 and are dependent on the activity of e1, but individually have a minimal or modest impact on SOX2 expression.…”
Section: Discussionsupporting
confidence: 91%
“…Lineage-specific oncogenes are known to be driven by condensed clusters of enhancer elements, namely super-enhancers or stretch enhancers 55 , 56 , 57 , yet the hierarchical structures for most of these enhancer clusters remain largely unknown. We show that the enhancer cluster co-amplified with SOX2 in squamous cancer is predominantly driven by a single enhancer e1, which aligns with previous findings of predominant enhancers in other enhancer clusters 58 , 59 . Within the SOX2 enhancer cluster, all the remaining enhancers physically interact with e1 and are dependent on the activity of e1, but individually have a minimal or modest impact on SOX2 expression.…”
Section: Discussionsupporting
confidence: 91%
“…This proposed model of activity is not unique to AR and a similar phenotype has been observed with several other transcription factors. Recent work using CRISPRi to knockout individual estrogen receptor binding sites demonstrated hierarchical or synergistic interactions between enhancers on gene expression [ 46 ]. In addition, work with the antigen receptor showed that both active and inactive enhancers are required for gene expression [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that the malignant transformation of breast epithelium was promoted by downregulating c-KIT expression (Chui 1996;Talaiezadeh et al 2012), and c-KIT could serve as a biomarker for atypical and malignancy proliferative ductal breast lesions (Janostiak et al 2018). Estrogen receptor 1 (ESR1) encodes an estrogen receptor that mediates the transcription of many estrogen-inducible genes essential for several reproductive functions, such as cell growth, metabolism, sexual development, and pregnancy, it is also expressed in other nonreproductive tissues such as bone (Bockers et al 2020;Carleton et al 2020;Pakharenko et al 2020). ESR1 mutations have proved to be a key factor in endocrine therapy resistance in BC with hormone receptor-positive.…”
Section: Discussionmentioning
confidence: 99%